PANEL RESPONSE: GROWTH POLICY - Honohan and the Comparative Perspective - O’Rourke, Kevin Hjortshøj (The Economic and Social Review, 2025)
It is highly appropriate to have an economic historian such as myself participating in a celebration of Patrick Honohan’s life and work. To most observers Patrick is a macroeconomist, financial economist, and central banker, and of course he has been all of those things in his time and an outstanding one to boot. But Honohan’s career is also deeply enmeshed with economic history. First, he has helped to make it, both when acting as advisor to Garrett FitzGerald in the 1980s, and in his role as Central Bank Governor during those very dark years that now (in part thanks to him) seem so long ago. Second, during the 2000s he wrote the first draft of the economic history of our crisis, in several frequently cited papers and reports that will be a key source for future historians (Honohan, 2009a; 2009b; 2010). And third, he has made fundamental contributions to Irish economic history (Honohan and Ó Gráda, 1998; Honohan and Walsh, 2002; FitzGerald and Honohan, 2023). This reflects a genuine interest in the past, which manifested itself inter alia during the regular cliometric workshops held at the Central Bank during his tenure there. Patrick has been an active and valued participant in many economic history meetings over the years, and economic historians are proud to have him as an honorary member of our tribe.